Implementasi Model Pembelajaran Course Review Horay (CRH) untuk meningkatkan Hasil Belajar Siswa kelas IVB SDN Brumbung Tahun Ajaran Gasal 2021/2022 - Nursiswati Prastiwi (Perkumpulan Kualitama Edukatika Indonesia, 2022)
Indonesian is a bridge between various things so that we can communicate, interact and understand each other. For this reason, it is very important for students to master Indonesian language skills. The aim of this research is to improve the learning outcomes of class IVB students at SDN Brumbung, Mranggen sub-district, Demak Regency for the odd school year 2021/2022. This research is Classroom Action Research (PTK) with 2 cycles, each cycle consisting of 4 stages. The results of this research are an increase in learning outcomes in Indonesian language subjects for class IV B students at SDN Brumbung for the 2021/2022 Odd Academic Year using the CRH cooperative learning model. The increase from cycle I with 17 students completing it with a percentage of 62.96% to 24 students with a percentage of 88.89% in cycle II.